Mother daughter revolution from betrayal to power - Debold, Elizabeth; Wilson, Marie; Malavé, Idelisse (Addison-Wesley, 1993)
For generations, women have unwittingly betrayed those they were trying to protect - their daughters - as they have handed down the same self-negating skills they themselves were taught to get along in our patriarchal society. In doing so, mothers were being asked to bear society's messages - messages they don't agree with themselves. How many women have tried to give their daughters loving advice, only to find they sound exactly like their mothers
Keywords: Feminists -- Family relationships -- United States; Mothers and daughters -- United States; Mutter; Tochter; USA